The Silent Revolution: How Wearable Technology is Redefining Health Monitoring - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The convergence of miniaturized sensors, advanced data analytics, and ubiquitous connectivity has ushered in a new era of personal health management. Wearabl...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care